The effect of Distributive Justice, Procedural Justice, and Interactional Justice on Job Satisfaction of Employees of The Tax Service Office (KPP) Pratama Sidoarjo Utara - Derry Marendra Firmansyah; Sundjoto Sundjoto; Sri Rahayu (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to analyze the influence of Distributive Justice, Procedural Justice, and Interactional Justice on the Job Satisfaction of employees at the North Sidoarjo Primary Tax Office (KPP Pratama Sidoarjo Utara). The research type is an influence study. The population in this research consists of 102 employees at KPP Pratama Sidoarjo Utara. The research sample was calculated using the Slovin formula, resulting in a sample size of 84. Data collection was conducted using a questionnaire, and variable measurement used the Likert scale. Data analysis utilized multiple linear regression and hypothesis testing. The research results form the regression equation as follows: Y = 1.641 + 0.203X1 + 0.225X2 + 0.489X3. The hypothesis testing results indicate that: 1) Distributive Justice, Procedural Justice, and Interactional Justice simultaneously have a significant influence on the Job Satisfaction of employees at the North Sidoarjo Primary Tax Office (KPP Pratama Sidoarjo Utara); 2) Distributive Justice partially has a significant influence on the Job Satisfaction of employees at the North Sidoarjo Primary Tax Office (KPP Pratama Sidoarjo Utara); 3) Procedural Justice partially has a significant influence on the Job Satisfaction of employees at the North Sidoarjo Primary Tax Office (KPP Pratama Sidoarjo Utara); 4) Interactional Justice partially has a significant influence on the Job Satisfaction of employees at the North Sidoarjo Primary Tax Office (KPP Pratama Sidoarjo Utara).